Detection of human papillomavirus DNA by polymerase chain reaction and southern blot hybridization in colorectal cancer patients - (:unkn) unknown (IMPRIMATUR PUBLICATIONS, 2009)
Purpose. The molecular mechanisms related to colorectal carcinogenesis are controversial. The purpose of this study was to evaluate the possible role of high-risk oncogenic human papillomavirus (HPV) types in the pathogenesis of colorectal cancer Patients and methods: Tumor, and corresponding normal mucosal tissue specimens were obtained soon after surgery from 56 patients with colorectal adenocarcinoma. We studied both neoplastic and normal colon tissues for the presence of HPV types 6, 11, 16, 18, and 33. After the isolation of DNA, the presence of specific types of HP V DNA was determined by polymerase chain reaction (PCR) and southern blot hybridization. Results: HPV DNA was detected in 46 (82.14%) of 56 colorectal adenocarcinomas and in 18 (32 %) of 56 normal colonic mucosal tissue samples. Two or more HPV types were detected in 32 carcinoma samples. HPV type 18 (n = 40) and 33 (h = 32) were the most frequently detected types of HPVs in the tumor tissues. None of the normal mucosal specimens revealed HP V 18 DNA. The expression rate of HPV DNA in tumor tissue was significantly higher than that encountered in normal colonic mucosa (p <0.001). Conclusion: Detection of HPV DNA types 18 and 33 in most of the colorectal adenocarcinoma specimens suggests that HP Vs may be related to carcinogenesis in glandular cells of the colorectal mucosa of our patient population.
Keywords: carcinoma; colon cancer; human papillomavirus; PCR; rectal cancer; viral association; EPIDERMAL-GROWTH-FACTOR; FACTOR RECEPTOR; CERVICAL NEOPLASIA; UTERINE CERVIX; HPV DNA; INFECTION; COLON; ASSOCIATION; CARCINOMA; TYPE-16